Problems of Learner-Centered Learning Practices among Islamic Studies Teachers in Intermediate and Secondary Stages in the Light of the Generative Constructivist Model - Al-Aosail , Abdulaziz Bin Faleh (Dirasat: Educational Sciences, 2024)
Objectives: The research aimed to identify the problems of learner-centered learning practices among Islamic Studies teachers in the intermediate and secondary stages in Al-Ahsa Governorate, in the light of the generative constructivist model. Methods: To achieve the research objectives, a descriptive-survery method was used. A questionnaire with 28 items distributed across four main areas of problems was administered. The sample included 186 teachers in the intermediate stage and 96 teachers in the secondary stage, totaling 282 teachers, selected randomly. Results:. The research found that the overall degree of the assessment of the problems of learner-centered learning practices among Islamic Studies teachers in the light of the generative constructivist model was "moderate" in both the intermediate and secondary stages. The overall mean was approximately 3.14 in the intermediate stage and 2.99 in the secondary stage. There were no statistically significant differences between the means of the sample members’ ratings of the problems in both stages, attributed to variables (educational stage and years of experience), except for the emergence of statistically significant differences attributed to the variable (years of experience) in the responses of intermediate stage teachers in the field of "learner-centered learning practices in the concentration stage," in favor of those with teaching experience of (10) years or more. ConclusionsThe research suggests enhancing Islamic Studies teachers’ awareness of employing learner-centered approaches for ongoing teaching improvement. It stresses the need to train supervisors in the generative constructivist model to foster such practices among teachers.